Storm surge associated with the Paradip cyclone of 1982 (MAUSAM, 1986)
Based on all avilable data from tide gauges and post storm surveys by India Meteorological Department and Government of Orissa; the correct magnitude of storm surge generated by the Paradip cyclone of 1982 has been obtained.